Effect of Bortezomib on hs-CRP Concentration in the Progression Stage of Atherosclerotic Rats (Future Science, 2022)
The mechanism of anti-atherosclerosis of bortezomib is thought to be through its anti-inflammatory. High-sensitivity C-Reactive Protein (hs-CRP) is an inflammation marker and an independent risk factor for atherosclerosis. This study aimed to analyze the effect of bortezomib on serum hs-CRP concentration in the progression stage of atherosclerotic rats. This study was an experimental study with a post-test only with a control design. This study used 15 male Wistar rats divided into three groups; group I was only given standard feed, group II was induced by vitamin D3 and an atherogenic diet, and group III was induced by vitamin D3 and given an atherogenic diet and bortezomib. Bortezomib 50 g/kg BW/day was administered on the first and third days. Serum hs-CRP concentration was measured using the ELISA technique. Statistical analyses to compare serum hs-CRP concentrations between groups were done using the ANOVA test followed by a post-hoc LSD test; p < 0.05 was considered statistically significant. The results showed that the induction of atherosclerosis resulted in 100% of atherosclerotic lesions in the progression stage. The highest hs-CRP concentration was found in group II (an average of 66.84 ng/mL) , followed by groups I (an average of 59.32 ng/mL) and III ( an average 49.43 ng/mL). The hs-CRP concentration in group III was significantly lower than in group II. It can be concluded that the administration of bortezomib could reduce hs-CRP concentration in the progression stage of atherosclerotic rats.